PENGEMBANGAN PERANGKAT PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEADS TOGETHER) UNTUK MELATIHKAN KETERAMPILAN BERKOMUNIKASI DAN MENINGKATKAN HASIL BELAJAR PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Hasnawati, Hasnawati; Agustini, Rudiana; Koestiari, Toeti (JPPS (Jurnal Penelitian Pendidikan Sains), 2015)
The aims of this study are to develop a cooperative learning type NHT (Numbered Heads Together). The typeis feasible (valid, practical, and effective) and can to practice communication skills, learning outcomes in the material of electrolyte and nonelectrolyte solution in the second semester students of class X State High School 1 Peso. Development of the learning is done based on the models of four-D. This study use done group pretest posttest design. Based on research data obtain findings: the validity of the research developed a good categorized; text book readability level students the developed a good category; good categorized enforceability of RPP; student?s dominant activity is to communicate information ideas/ opinions, ask questions, and presentations with the percentage of 18.88%; the obstacles encountered during the implementation of the learning device that students are not familiar with the cooperative model type NHT (Numbered Heads Together) and the majority of students are less active in the learning process; students responded positively to the learning process; teaching and learning process using cooperative learning type NHT (Numbered Heads Together) is able to practice the students communication skills; and student learning outcomes after participating in the learning process is completed 100%. The conclusion of this studyis the cooperative learning type NHT (Numbered Heads Together) feasible (valid, practical, andeffective) used to practice communication skills and learning out comes on the material of electrolyte and nonelectrolyte solution. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran kooperatif tipe NHT (Numbered Heads Together) yang layak (valid, praktis, dan efektif), melatihkan keterampilan berkomunikasi serta mengetahui hasil belajar pada materi larutan elektrolit dan nonelektrolit pada siswa kelas X semester II SMA Negeri 1 Peso. Pengembangan perangkat pembelajaran dilakukan berdasarkan model four-D. Rancangan penelitian menggunakan One Group Pretest-Posttest Design. Berdasarkan data penelitian diperoleh beberapa temuan:validitas perangkat pembelajaran yang dikembangkan berkategori baik; tingkat keterbacaan Buku Ajar Siswa yang dikembangkan berkategori tepat untuk pembelajaran; keterlaksanaan RPP berkategori baik; aktivitas siswa yang dominan adalah mengkomunikasikan informasi ide/pendapat, bertanya, dan presentasi dengan persentase 18,88%; hambatan yang ditemui selama penerapan perangkat pembelajaran yaitu siswa belum terbiasa dengan model kooperatif tipe NHT (Numbered Heads Together) dan sebagian siswa kurang aktif dalam proses pembelajaran; siswa memberikan respon positif terhadap proses pembelajaran; pembelajarankooperatif tipe NHT(Numbered Heads Together) dapat melatihkan keterampilan berkomunikasi siswa; dan hasil belajar siswa setelah mengikuti proses belajar mengajar adalah tuntas 100%.  Kesimpulan dari penelitian ini adalah perangkat pembelajaran kooperatif tipe NHT (Numbered Heads Together) layak (valid, praktis, dan efektif) digunakan untuk melatihkan keterampilan berkomunikasi dan hasil belajar pada materi larutan elektrolit dan nonelektrolit.